SPEED CONTROL OF AN ATHLETE IN THE DEVELOPMENT OF HIS PHYSICAL QUALITIES - Amangul Saparbayevna Yusupbayeva (European Science Publishing, 2024)
The article presents the most reliable tests for opening samples measured by mechanical dynamometers. Parameters such as strength gradients and maximum strength measured by strain gauge systems are characterized by relatively high reliability.
Keywords: Sport, speed, quality, reaction, maximum speed, endurance, flexibility, strength.